2018
DOI: 10.2337/dc17-2682
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Reduction in Severe Hypoglycemia in Adults With Type 1 Diabetes Complicated by Impaired Awareness of Hypoglycemia: Two-Year Follow-up in the HypoCOMPaSS Randomized Clinical Trial

Abstract: Optimized insulin replacement and glucose monitoring underpinned by hypoglycemia-focused structured education should be provided to all with type 1 diabetes complicated by impaired awareness of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 33 publications
3
65
0
2
Order By: Relevance
“…Therefore, the device represents a cost-effective measure to reducing hypoglycemia, particularly in high-risk groups of patients. Moreover, these data further support the use of continuous glucose data to reduce hypoglycemia in diabetes 2–4 19 20…”
Section: Resultssupporting
confidence: 58%
“…Therefore, the device represents a cost-effective measure to reducing hypoglycemia, particularly in high-risk groups of patients. Moreover, these data further support the use of continuous glucose data to reduce hypoglycemia in diabetes 2–4 19 20…”
Section: Resultssupporting
confidence: 58%
“…For example, a UK-based structured education program, Dose Adjustment for Normal eating (DAFNE), restores awareness in 43% of people with impaired awareness of hypoglycaemia [27]. Similarly, the HypoCOMPaSS trial showed that education around the prompt treatment of hypoglycaemia was as important as technologies such as insulin pump therapy and glucose sensors [28]. • Insulin pumps and continuous glucose sensors: insulin pump therapy, particularly sensor-augmented insulin pumps, has a role in reducing severe hypoglycaemia and restoring unawareness [29].…”
Section: Reversing Hypoglycaemic Unawarenessmentioning
confidence: 99%
“…Continuous glucose monitoring in pregnant women with type 1 diabetes (CONCEPTT): a multicentre international randomised controlled trial Feig DS 1,2,3 , Donovan LE 4 , Corcoy R 5 , Murphy KE 2,3,6 , Amiel SA 7 , Hunt KF 7,8 , Asztalos E 9 , Barrett JFR 9 , Sanchez JJ 9 , de Leiva A 5 , Hod M 10 , Jovanovic L 11,12 , Keely E 13 This manuscript is also discussed in the article on Technology and Pregnancy, page S-101.…”
Section: Commentsmentioning
confidence: 99%